Registration of 'Vision 45' Wheat. Issue 3 (17th July 2015) - Liu, L.; Barnett, M. D.; Griffey, C. A.; Malla, S.; Brooks, W. S.; Seago, J. E.; Thomason, W. E.; Rucker, E.; Behl, H. D.; Pitman, R. M.; Dunaway, D. W.; Vaughn, M. E.; et al.
Abstract : 'Vision 45' (Reg. No. CV‐1110, PI 667642), is a hard red winter (HRW) wheat ( Triticum aestivum L.) cultivar that was developed and tested as VA07HRW‐45 and released by the Virginia Agricultural Experiment Station in 2012. Vision 45 was derived from the cross 'Provinciale'/'Vision 10' using a modified bulk breeding method. It was tested in replicated yield trials in Virginia (2008–2014) and in the USDA‐ARS Uniform Bread Wheat (UBW) Trials (2009–2014). Vision 45 is a widely adapted, high‐yielding, awned, semidwarf (unknown Rht gene) HRW wheat with mid‐ to late‐season spike emergence, strong straw strength, and resistance or moderate resistance to diseases prevalent in the mid‐Atlantic region. In Virginia, Vision 45 was the highest‐yielding hard winter wheat over a 4‐yr period, having an average grain yield (5499 kg ha −1 ) that was slightly higher than the soft red winter wheat cultivar Tribute (PI 654422), which was 5181 kg ha −1 . Over 6 yr and 97 environments in the UBW Trials, Vision 45 had an average grain yield of 4924 kg ha −1, one of the highest‐yielding hard wheat cultivars. Vision 45 has good end‐use quality on the basis of comparisons with the HRW wheat check cultivar Jagger (PI 593688), for flour yield (70.7 versus 70.3 g 100 g −1 ), flour protein (10.5 versus 10.6 g 100 g −1 ), flour water absorption (60.7 vs. 61.3 g 100 g −1 ), dough mixing tolerance (2.7 versus 2.7), pup‐loaf volume (798 versus 773 cm 3 ), and crumb grain scores (3.3 versus 2.8).